Quit attempts and tobacco abstinence in primary care patients: follow-up of a pragmatic, two-arm cluster randomised controlled trial on brief stop-smoking advice – ABC versus 5As. Issue 3 (26th July 2021) - Kastaun, Sabrina; Viechtbauer, Wolfgang; Leve, Verena; Hildebrandt, Jaqueline; Funke, Christian; Klosterhalfen, Stephanie; Lubisch, Diana; Reddemann, Olaf; Raupach, Tobias; Wilm, Stefan; Kotz, Daniel
We developed a 3.5-h training for general practitioners (GPs) in delivering brief stop-smoking advice according to different methods (ABC, 5As). In a pragmatic, cluster randomised controlled trial our training proved effective in increasing GP-delivered rates of such advice (from 13% to 33%). In this follow-up analysis we examined the effect of the training and compared ABC versus 5As on patient-reported quit attempts and point prevalence abstinence at weeks 4, 12 and 26 following GP consultation. Follow-up data were collected in 1937 smoking patients – independently of the receipt of GP advice – recruited before or after the training of 69 GPs. At week 26, ∼70% of the patients were lost to follow-up. All 1937 patients were included in an intention-to-treat analysis; missing outcome data were imputed. Quit attempts and abstinence rates did not differ significantly from pre- to post-training or between patients from the ABC versus the 5As group. However, ancillary analyses showed that patients who received GP advice compared to those who did not had two times higher odds of reporting a quit attempt at all follow-ups and abstinence at week 26. We reported that our training increases GP-delivered rates of stop-smoking advice, and the present analysis confirms that advice is associated with increased quit attempts and abstinence rates in patients. However, our training did not further improve these rates, which might be related to patients' loss to follow-up or to contextual factors, e.g. access to free evidence-based cessation treatment, which can hamper the transfer of GPs' advice into patients' behaviour change. GP-delivered brief stop-smoking advice increases smoking patients' quit attempts and abstinence rates. 3.5 h GP training in providing such advice according to the ABC versus 5As method increases advice rates. https://bit.ly/2SM3on4